NMDA and non-NMDA glutamate receptors in auditory transmission in the barn owl inferior colliculus - Feldman, DE (J Neurosci, 1994)
The pharmacology of auditory responses in the inferior colliculus (IC) of the barn owl was investigated by iontophoresis of excitatory amino acid receptor antagonists into two different functional subdivisions of the IC, the external nucleus (ICx) and the lateral shell of the central nucleus (lateral shell), both of which carry out important computations in the processing of auditory spatial information. Combined application of the NMDA receptor antagonist 2-amino-5-phosphonovaleric acid (AP5) and the non-NMDA receptor antagonist 6-cyano-5-nitroquinoxaline-2,3- dione (CNQX) significantly reduced auditory-evoked spikes at all sites in these two subdivisions, and completely eliminated responses at many locations. This suggests that excitatory amino acid receptors mediate the bulk, if not all, of auditory responses in the ICx and lateral shell. NMDA and non-NMDA receptors contributed differently to auditory responses in the two subdivisions. In the ICx, AP5 significantly reduced the number of auditory-evoked spikes at every site tested. On average, AP5 eliminated 55% of auditory-evoked spikes at multiunit sites and 64% at single-unit sites in this structure. In contrast, in the lateral shell, AP5 significantly reduced responses at less than half the sites tested, and, on average, AP5 eliminated only 19% of spikes at multiunit sites and 25% at single-unit sites. When the magnitude of response blockade produced by AP5 at individual multiunit sites was normalized to adjust for site-to-site differences in the efficacy of iontophoresed AP5 and CNQX, AP5 blockade was still significantly greater in the ICx than the lateral shell. CNQX application strongly reduced responses in both subdivisions. These data suggest that NMDA receptor currents make a major contribution to auditory responses in the ICx, while they make only a small contribution to auditory responses in the lateral shell. Non-NMDA receptor currents, on the other hand, contribute to auditory responses in both subdivisions, and mediate the bulk of auditory transmission in the lateral shell. The time course of the NMDA receptor contribution to ICx auditory responses and the dependence of this contribution on stimulus level were both examined in detail. AP5 preferentially blocked spikes late in ICx auditory responses, while CNQX blocked spikes equally throughout the responses. This pattern is consistent with a simple model in which slow NMDA receptor currents and faster non-NMDA receptor currents are both activated by auditory inputs to ICx neurons.